Comparative analysis of Front-End Code Playground tools - Magier, Mateusz; Pańczyk, Beata (Journal of Computer Sciences Institute, 2018)
This article contains comparative analysis of selected Front-End Code Playground tools. The included tables were performed on the results of tests of the considered applications and the analysis of their documentation. The comparison was made for several criteria (including: features of code editors, custom modes of creating projects, support for preprocessors and project export methods). The conclusions drawn from the comparison allowed dividing the considered tools into three groups (applications with: high, moderate and low level of advancement).